Essential Role of Sperm-Specific PLC-Zeta in Egg Activation and Male Factor Infertility: An Update - Saleh, Alaaeldin; Kashir, Junaid; Thanassoulas, Angelos; Safieh-Garabedian, Bared; Lai, F. Anthony; Nomikos, Michail (Frontiers in Cell and Developmental Biology, 2020)
Sperm-specific phospholipase C zeta (PLCζ) is widely considered to be the physiological stimulus responsible for generating calcium (Ca2+) oscillations that induce egg activation and early embryonic development during mammalian fertilization. In the mammalian testis, PLCζ expression is detected at spermiogenesis following elongated spermatid differentiation. Sperm-delivered PLCζ induces Ca2+ release via the inositol 1,4,5-trisphosphate (InsP3) signaling pathway. PLCζ is the smallest known mammalian PLC isoform identified to date, with the simplest domain organization. However, the distinctive biochemical properties of PLCζ compared with other PLC isoforms contribute to its unique potency in stimulating cytosolic Ca2+ oscillations within mammalian eggs. Moreover, studies describing PLCζ ‘knockout’ mouse phenotypes confirm the supreme importance of PLCζ at egg activation and monospermic fertilization in mice. Importantly, a number of clinical reports have highlighted the crucial importance of PLCζ in human fertilization by associating PLCζ deficiencies with certain forms of male factor infertility. Herein, we give an update on recent advances that have refined our understanding of how sperm PLCζ triggers Ca2+ oscillations and egg activation in mammals and we discuss the nature of a potential second ‘alternative’ sperm factor, the PLCζ localization in mammalian sperm and the direct links observed between defective PLCζ protein in the sperm and documented cases of male infertility. Furthermore, we postulate how this sperm protein can be used as a potential diagnostic marker, and also as a powerful therapeutic agent for treatment of certain types of male infertility due to egg activation failure or even in more general cases of male subfertility.